The Laminin-α1 Chain-Derived Peptide, AG73, Binds to Syndecans on MDA-231 Breast Cancer Cells and Alters Filopodium Formation - Madhavi Puchalapalli; Liang Mu; Chevaunne Edwards; Benjamin Kaplan-Singer; Pearl Eni; Kiran Belani; David Finkelstein; Arpan Patel; Megan Sayyad; Jennifer E. Koblinski (Analytical Cellular Pathology)
Breast cancer is one of the most common forms of cancer affecting women in the United States, second only to skin cancers. Although treatments have been developed to combat primary breast cancer, metastasis remains a leading cause of death. An early step of metastasis is cancer cell invasion through the basement membrane. However, this process is not yet well understood. AG73, a synthetic laminin-α1 chain peptide, plays an important role in cell adhesion and has previously been linked to migration, invasion, and metastasis. Thus, we aimed to identify the binding partner of AG73 on breast cancer cells that could mediate cancer progression. We performed adhesion assays using MCF10A, T47D, SUM1315, and MDA-231 breast cell lines and found that AG73 binds to syndecans (Sdcs) 1, 2, and 4. This interaction was inhibited when we silenced Sdcs 1 and/or 4 in MDA-231 cells, indicating the importance of these receptors in this relationship. Through actin staining, we found that silencing of Sdc 1, 2, and 4 expression in MDA-231 cells exhibits a decrease in the length and number of filopodia bound to AG73. Expression of mouse Sdcs 1, 2, and 4 in MDA-231 cells provides rescue in filopodia, and overexpression of Sdcs 1 and 2 leads to increased filopodium length and number. Our findings demonstrate an intrinsic interaction between AG73 in the tumor environment and the Sdcs on breast cancer cells in supporting tumor cell adhesion and invasion through filopodia, an important step in cancer metastasis.